1
$\begingroup$

I have the equation:

$\left (\sqrt{3+2\sqrt{2}} \right )^x- \left (\sqrt{3-2\sqrt{2}} \right )^x=\frac{3}{2}$

I wrote the left side of the equation as square roots.

$(1+\sqrt{2})^x-(1-\sqrt{2})^x=\frac{3}{2}$

How do I found out the final solution? Thank you very much!

P.S. The answers I can choose from are:

a) $x=1$

b) $x=2$

c) $x=\frac{2\lg2}{\lg(3+2\sqrt2)}$

d) $x=\frac{2\lg2}{\lg(3-2\sqrt2)}$

e) no solution

f) $x=2\lg2$

$\endgroup$
  • $\begingroup$ The key structural thing is that $3-2\sqrt{2}=\frac{1}{3+2\sqrt{2}}$. $\endgroup$ – André Nicolas Jul 18 '12 at 12:35
5
$\begingroup$

First of all, $\sqrt{3-2\sqrt{2}}$ is $\sqrt{2} - 1$.

Now, Let $(\sqrt{2}+1)^x$ be y.

$y - \frac{1}{y} = \frac{3}{2}$.

So $2y^2 - 3y - 2 = 0$.

So y is 2 or $-\frac{1}{2}$. As y = $(\sqrt{2}+1)^x$, y must be positive and thus 2.

$(\sqrt{2}+1)^x = 2$

So $x = \frac{log(2)}{log(\sqrt{2}+1)}$, which is same as option c) here as you can see by simplifying the expression in c). I guess they are also taking lg instead of log, but as you can see it makes no difference whatsoever.

$\endgroup$
  • $\begingroup$ Can you please explain why the $(\sqrt2-1)^x$ is $\frac{1}{y}$ and the transformation of x into $log$? Thank you very much for your help! $\endgroup$ – Grozav Alex Ioan Jul 18 '12 at 9:52
  • $\begingroup$ $\sqrt{2}-1$ is inverse of $\sqrt{2}+1$, so $(\sqrt{2}-1)^x$ is inverse of $(\sqrt{2}+1)^x$. For the other question, if $a^x=b$, then by taking log on both sides, $x log(a) = log(b)$. Therefore $x = \frac{log(b)}{log(a)}$. $\endgroup$ – Wonder Jul 18 '12 at 9:57
1
$\begingroup$

$$(\sqrt{3+2\sqrt{2}})^x-(\sqrt{3-2\sqrt{2}})^x=\frac{3}{2}$$

Multiply both side with $(\sqrt{3+2\sqrt{2}})^x$, then you get

$$(\sqrt{3+2\sqrt{2}})^{2x}-(\sqrt{(3-2\sqrt{2})(3+2\sqrt{2})})^x=\frac{3}{2}(\sqrt{3+2\sqrt{2}})^x$$

$$(\sqrt{3+2\sqrt{2}})^{2x}-(1)^x=\frac{3}{2}(\sqrt{3+2\sqrt{2}})^x$$

Let $y =(\sqrt{3+2\sqrt{2}})^x$, then $y^2 -1 = \frac{3}{2}y$

Solve above equation, $y =2$ or $y = \frac{-1}{2}$(its never true)

Therefore, $y =2$ that implies $(\sqrt{3+2\sqrt{2}})^x =2$

Apply $log$ both side,$$x\log(\sqrt{3+2\sqrt{2}}) =log(2)$$

Therefore, $$x=\frac {2\log(2)}{\log({3+2\sqrt{2}})}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.